What leads to direct epoxidation? an exhaustive DFT investigation of electrophilic oxygen mediated epoxidation of ethylene on Ag(100) - Nair, Aathira; Joshi, Kavita (Computational Materials Science, 2024)
Extensive research has contributed to a better understanding of the commercially important epoxidation reaction. Selectivity, a crucial aspect of this reaction, has received significant attention in both experimental and theoretical investigations. However, a consensus regarding the role of electrophilic oxygen in epoxidation is yet to be reached. The present study is a theoretical examination of the prerequisites necessary for direct epoxidation to occur on the Ag(100) surface, at varied monolayer concentrations. Additionally, the study investigates the characteristics of various oxygen species interacting with ethylene to promote the direct epoxidation pathway. Based on the effective charges and projected density of states (pDOS) analysis, three oxygen variants were identified on the Ag(100) surface: atomic oxygen, dissociatively adsorbed molecular oxygen, and O 3 . The investigation reveals that all oxygen species, despite their physical and electronic differences, are electrophilic and undergo direct epoxidation. This work provides insights into the complex nature of epoxidation reaction and discusses electronic factors influencing the selective oxidation route on different Ag-O complexes.
Keywords: Ag(100); DFT; Direct epoxidation; Electrophilic oxygen; Ethylene Oxide (EtO); OMC

When facets meet impurities: Trace gas dominance over CO2 adsorption on ZnO - Bhati, Meema; Joshi, Kavita (Applied Surface Science, 2026)
The catalytic hydrogenation of CO2 to methanol using Cu-ZnO/Al2O3 (CZA) is a key route for sustainable chemical production, when coupled with CO2-rich industrial off-gases. However, trace secondary gases, though present only at ppm levels, can poison active sites and suppress catalytic performance. In this work, we employ periodic density functional theory (DFT) to investigate interactions of H2S, SO2, NO2, NO, CO and CH4 with ZnO surfaces:(10(-)10), (10(-)11), (11(-)20), (10(-)13), and (11(-)22), and compared their adsorption pattern with CO2, the principle component of methanol synthesis. H2S dissociates on all the surfaces, SO2, and NO2 are chemisorbed, CH4 remains physisorbed, and NO, CO, and CO2 exhibit facet-dependent adsorption. Electronic structure analysis reveal that chemisorption occurs when surface energy states near the Fermi level overlap with HOMO of adsorbate, enabling charge transfer, whereas physisorption lacks such overlap. The adsorption strength follows the order: H2S SO2 NO2 NO CO CO2 CH4, suggesting that sulfur and nitrogen containing species exhibit strong chemisorption and compete with CO2 for active sites, potentially impacting the efficiency of methanol synthesis. These insights provide an atomic scale understanding of impurity-surface interactions and highlight potential role of ZnO as an efficient feed stock purifier for CO2-rich gas streams.
Keywords: CZA catalyst; flue gases; Valorization of CO2; ZnO